Peningkatan Proses dan Hasil Belajar IPAS Peserta Didik Menggunakan Model Project Based Learning - Siska Siska; Subhanadri Subhanadri; Zulqoidi R. Habibie (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research was motivated by the low learning process and outcomes of fourth-grade students at SDN 31/VI Rantau Panjang in the IPAS subject, as indicated by low mastery learning and lack of active participation during the learning process. The aim of this study is to describe the improvement in students’ learning process and cognitive achievement through the implementation of the Project Based Learning (PjBL) model in the IPAS subject. The method used was Classroom Action Research (CAR), carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 20 fourth-grade students. Data were collected using observation sheets and cognitive learning tests. The results showed that the PjBL model improved student engagement and motivation in the classroom. In Cycle I, the mastery learning rate reached 77,27%, which increased to 90,91% in Cycle II. Student activity and collaboration also improved significantly, as evidenced by observation results. It can be concluded that the Project Based Learning model is effective in enhancing both the learning process and learning outcomes in IPAS. The future prospect of this model is its potential to foster meaningful, collaborative, and student-centered learning across various subjects at the elementary level.